An Analysis Of Go-Food, Grabfood, And Shopeefood Utilization To Improve Customer Loyalty On Home-Based Business Owners In Tangerang City - Maria Oktaviana; Andres Dharma Nurhalim; Erni Hernawati (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The development of technology and information plays an important role in economic development. Advances in technology and information continue to encourage economic development, especially in business activities. The type of business that is currently being favored by the community is the culinary business by opening a restaurant business. The high level of community activity and demands for speed and time efficiency make the restaurant business considered a big opportunity at this time. The purpose of this study was to determine the use of go-food, grabfood and shopeefood applications in increasing consumer loyalty to restaurant business owners in the city of Tangerang. The method used in this study is multiple linear regression analysis and different tests that function to determine whether there are differences in consumer loyalty to restaurant business owners in the city of Tangerang after and before using the Go-food, Grabfood and Shopeefood applications. In accordance with what has been tested, it is found that the price, number of orders and length of operating hours simultaneously have a positive and significant effect on consumer loyalty and it is found that there are differences in loyalty after and before using the Go-food, Grabfood and Shopeefood applications.